Klasifikasi Tingkat Stres Akademik dan Gambaran Mekanisme Koping Mahasiswa - Sari, Dita Dwi Wulan; Marsisno, Waris (Politeknik Statistika STIS, 2023)
Stress is a natural thing and often encountered in life. Stress can also occur in an academic environment (academic stress). Academic stress occurs due to the inability of students to adapt to lecture conditions. Changes in teaching and learning activities due to Covid-19 can also trigger academic stress. Therefore, it is important for students to have good problem management (coping mechanisms) in dealing with stress. This study aims to describe the level of academic stress and coping mechanisms for Polstat STIS T.A 2022/2023 students along with their classifications. The research was conducted on 360 Polstat STIS students T.A 2022/2023 using an instrument in the form of an online questionnaire. Data analysis in this study uses the decision tree algorithm C5.0. The results showed that 70.6 percent of students were at moderate stress levels. The most influential variable in moderate stress levels is intrapersonal (34.22 percent). As many as 51.39 percent of students use adaptive coping mechanisms with influential indicators namely restrain coping, planning, active coping and acceptance. The stress level decision tree model produces an accuracy of 96.1 percent with a tree size of 23.